Volume Measurements of Normal Orbital Structures by Computed Tomographic Analysis - Forbes, Glenn; Gehring, Dale G.; Gorman, Colum A.; Brennan, Michael D.; Jackson, Ian T. (American Journal of Neuroradiology, 1985)
Computed tomographic digital data and special off-line computer graphic analysis were used to measure volumes of normal orbital soft tissue, extraocular muscle, orbital fat, and total bony orbit in vivo in 29 patients (58 orbits). The upper limits of normal for adult bony orbit, soft tissue exclusive of the globe, orbital fat, and muscle are 30.1 cm3, 20.0 cm3, 14.4 cm3, and 6.5 cm3, respectively. There are small differences in men as a group compared with women but minimal difference between right and left orbits in the same person. The accuracy of the techniques was established at 7%–8% for these orbit structural volumes in physical phantoms and in simulated silicone orbit phantoms in dry skulls. Mean values and upper limits of normal for volumes were determined in adult orbital structures for future comparison with changes due to endocrine ophthalmopathy, trauma, and congenital deformity.